Global DNA 5‐Hydroxymethylcytosine and 5‐Formylcytosine Contents Are Decreased in the Early Stage of Hepatocellular Carcinoma - Liu, Jiao; Jiang, Jinhua; Mo, Jiezhen; Liu, Dan; Cao, Dan; Wang, Hailin; He, Yufei; Wang, Hongyang (Hepatology (Baltimore, Md.), 2019)
Methylation of the fifth position of cytosine (5mC) is an important epigenetic modification of DNA. It has been shown that the oxidized derivatives of 5mC, namely 5‐hydroxymethylcytosine (5hmC), 5‐formylcytosine (5fC), and 5‐carboxylcytosine (5caC), are in dynamic existence and have distinct regulatory functions. In the current study, we investigated whether there are changes in the contents of all three 5mC‐oxidized derivatives in the hepatocellular carcinoma (HCC) genome and further explored the underlying mechanisms. We showed that both global genomic 5hmC and 5fC contents were decreased significantly in the very early stage (stage 0, Barcelona Clinic Liver Cancer [BCLC] staging) of HCC compared with those of paratumor tissues. Noteworthily, 5fC content continued to decrease in the late stage (BCLC staging from 0 to A) of HCC. The 5caC content in HCC tissues was below the detection threshold. Hepatitis B virus (HBV) infection was associated with 5mC, 5hmC, or 5fC decrease in HCC; and measurements in cell lines integrated with or without HBV DNA showed consistent results. On the other hand, both the expression level of ten‐eleven translocation enzyme 2 (TET2) and α‐ketoglutarate content were decreased significantly in HCC. The significantly positive correlations among the expression levels of DNA methylation–related enzymes in paratumor tissues were generally attenuated or even disappeared in HCC tumor tissues. The decreases of both 5hmC and 5fC contents in genomic DNA were associated with poor prognosis of HCC patients. Conclusion: Global 5hmC and 5fC contents were decreased significantly in the very early stage of HCC; the decrease of 5hmC and 5fC was mainly due to the decrease of 5mC and associated with HBV infection, decreased TET enzyme activity, and uncoordinated expression of DNA methylation–related enzymes.